HOMUNCULUS Bearing Incorporeal Arcticulations - Vola, Joonas (fi=Lapin yliopisto|en=University of Lapland|, 2022)
This dissertation studies ‘the Arctic in Change’. In contrast to a traditional research setting, its aim is to engage with questions that respond to both ‘the Arctic’ and ‘in Change’ as preformed answer and outcome. Since ‘the Arctic’ is not constituted by a single definition, mode, science, art, discipline, method, state, continent, image, symbol, instance, agent or unit, it is considered and treated with the means and matters of bricolage in the spirit of post-qualitative inquiry. Accordingly, this approach requires involvement from a multiplicity of theoretical, methodological and research material: the intra-actions of performativity theory, the genealogy of discursive material practices, studies on perception, visual culture, aesthetics and ethics, art & design, ecology and ethology, as well as the politics residing in them. Furthermore, the recognition of the partiality, influence and agency of the elements constituting this study beyond the rationalised and controlled research design requires a more fluid manner of writing, deriving from the ideals of writerly and open text, infused with inter- and intratextuality and co-conducted in phenomenological writing to produce a novel conduct in avoiding firm structuring and hierarchy while pursuing open-ended objectives. The analysis begins by compromising the cohesion of Arctic representations as objects with unaltered identities, exhibiting a diorama of a polar bear. The seemingly neutral and passive object occupies several inherited subject positions that emerge from it as material outcomes. The representation holds the capacity to record the audience’s corporeality through sensory and motoric traces and to perform through their bodies as fixed prepositions. The encounter endangers and re-establishes the participatory subject and object positions as co- and counter to each other. How representations are conducted is foremost a question of the manipulation of distance, which proceeds from aesthetics to epistemological and ontological conditions. Different ...